Hubungan Pola Asuh Orangtua Dengan Perkembangan Sosial Anak Penyandang Disabilitas Di SLBN Surade Kabupaten Sukabumi - Johan Budhiana; Taufik Mu`zizat Nugroho; Rima Novianti Utami (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2022)
Children's social development is influenced by parenting patterns. A good relationship between children and their parents will create a sense of affection, where children will be more open in interacting because of the establishment of good relationships that are supported by proper communication. The purpose of the study was to determine the relationship between parenting patterns and the social development of children with disabilities. Parenting is a whole interaction, where parents intend to stimulate their children by changing the behavior, knowledge and values ​​that are considered the most appropriate by parents, so that children can be independent, grow and develop in a healthy and optimal manner. Social development is the level of interaction of children with other people, ranging from parents, siblings, playmates, to society at large. Types of correlational research. The population is all parents in SLBN Surade Sukabumi Regency with a sample of 48 people. Sampling using Total Sampling. Data analysis using Chi-Square test. The results showed that most of the respondents rated the children's social development as high and had a democratic parenting style. There is a significant relationship between parenting and social development (p=002). The conclusion is that there is a relationship between parenting and social development of children with disabilities at SLBN Surade, Sukabumi Regency. It is hoped that the Surade Health Center can hold a special training program for parents regarding good parenting for the developmental needs of children with disabilities.